THE EFFECT OF CHITOSAN ON THE HEMOTOLOGICAL INDICATORS AND BODY GROWTH DYNAMICS OF KARAKUL LAMBS (Universal International Scientific Journal, 2026)
This article presents the results of a study conducted to study the effects of chitosan on body weight growth dynamics and hematological parameters of Karakul lambs. The results of the study provide scientific justification for the prospects for the use of chitosan as a biological supplement and prophylactic agent.
Keywords: Erythrocytes; leukocytes; hemoglobin